Projecting future climate change impacts on the distribution of the ‘Octopus vulgaris species complex’ - Borges, Francisco Oliveira; Guerreiro, Miguel; Santos, Catarina Pereira; Paula, José Ricardo; Rosa, Rui (Frontiers in Marine Science, 2022)
Introduction Historically considered to be a single cosmopolitan species, the so called Octopus vulgaris species complex (OVSC) is now recognized to be a group of (at least) six cryptic species: O. americanus (in the west Atlantic), O. vulgaris (in the northeast Atlantic and Mediterranean Sea), O. aff. vulgaris (in the region of South Africa), O. tetricus (southeastern Oceania), O. sinensis (northwestern Pacific), and O. djinda (western Australia). The potentially different environmental preferences of this highly cryptic species complex may result in distinct consequences under future environmental conditions. Methods The present study employed species distribution models (SDM) using MaxEnt to investigate potential changes in habitat suitability and geographical distribution of the OVSC in the future (i.e., 2050, and 2100), across four representative concentration pathway scenarios (RCP-2.6, 4.5, 6.0, and 8.5, CMIP5). Results Differential responses were observed in the OVSC species analyzed. Specifically, O. vulgaris and O. tetricus exhibited a severe loss in distribution across their predicted range; O. americanus exhibited projected extirpation close to the equator, with limited expansion towards the poles; O. aff. vulgaris was projected to lose half of its current distribution; O. sinensis exhibited moderate losses, with projected increases in northern areas; and finally, O. djinda exhibited limited losses to its distribution. Except for O. sinensis, increasing RCP severity exacerbated changes in mean habitat suitability and projected distribution gains and losses. Discussion Ultimately, this study provides information on the potential biogeographical effects of marine climate change on a key worldwide ecological and economic resource to further disentangle the effects over each OVSC species, with the goal of assisting toward the sustainable management of octopus species at the global scale.